Trace elements (As, Co, Cu, Mo, Ni, U) at IODP Site U1417 sediments - Zindorf, Mark; März, Christian (PANGAEA, 2025)
This dataset compiles XRF trace metal data from sediments from IODP Site U1417 (this dataset) and basement material from DSDP Site 178 (doi:10.1594/PANGAEA.975180; ~1.5 km spatial distance) in the Gulf of Alaska. IODP Data stem from IODP Expedition 341 (Joides Resolution), DSDP Data stem from Leg 18 (Glomar Challenger). The data were produced with wavelength-dispersive X-ray fluorescence (XRF; Panalytical Axios max, 3 kW). The area is characterized by fluid circulation at the sediment-basement interface caused by subduction-related plate bending. The circulating fluids install a reverse sulfate-methane transition zone (SMTZ) in the sediments with sulfate diffusing upwards from the bottom of the sediment succession. The accompanying publication investigates causes for unusual trace element enrichments at Site U1417 and especially in the deep SMTZ and the potential leaching and re-distribution of elements from the basaltic basement into the sediments by the deep aquifer.
Keywords: diagenetic enrichment; fluid circulation; IODP; sediment-basement interface; trace metals